Analyzing Literacy on Weather-Related Hazards and Risks among Students of an Eastern Mediterranean Region - Katerina Papagiannaki; Kyriaki Makri; Vassiliki Kotroni; Konstantinos Lagouvardos (GeoHazards, 2024)
The present study analyzes students’ weather-related hazard and risk literacy in Greece, a climate change hotspot region in the Eastern Mediterranean. In this context, we examine the students’ level in two core literacy variables, namely knowledge and competency. In addition, we explore how knowledge, attitudes, and socio-demographic variables influence students’ competencies related to weather and climate risk assessment and adaptability. A questionnaire-based survey was conducted on 474 students aged 12–16. The regression results showed that knowledge significantly affects the level of competency. Self-belief and confidence in science were the most influential among the attitudinal variables. We conclude by discussing the educational and behavioral issues highlighted as essential to address them with targeted policies and measures in formal education complemented by non-formal educational activities. We also propose future education requirements like further integration of real-world applications and advanced technologies to enhance students’ literacy in weather-related hazards and risks.